Preparation of ultra-thick β-SiC films using different carbon sources. (December 2015) - Tu, R.; Zheng, D. H.; Cheng, H.; Han, M. X.; Zhang, S.; Goto, T.
Abstract : Polycrystalline ultra-thick β-SiC films have been grown on graphite substrates via halide chemical vapour deposition method by using tetrachlorosilane (SiCl4 ) as silicon source, whereas methane (CH4 ), acetylene (C2 H2 ), propane (C3 H8 ) and liquid petroleum gas as carbon sources, respectively. The effects of deposition temperature ( T dep ) and carbon source on the orientations, microstructures and deposition rate ( R dep ) were investigated. R dep of β-SiC films dramatically increased with increasing T dep . In the case of C2 H2, it provides a sufficient source of carbon and results in the maximum R dep under identical T dep compared to the other carbon sources. Conversely, CH4 decomposition in the Si–C–Cl–H system was proved to be inactive with SiCl4 in the entire range of T dep . The orientations of the β-SiC films transform from 〈111〉 to random to 〈110〉 with increasing T dep, and highly 〈111〉- and 〈110〉-oriented β-SiC films were fabricated at 1473 and 1773 K, respectively.